1998
DOI: 10.1007/s007020050119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repeated immobilization on serotonin metabolism in different rat brain areas and on serum corticosterone

Abstract: The effect of daily repeated 10 min immobilization on the serotoninergic neurotransmission and serum corticosterone levels was studied. Male Lewis rats were immobilized for a 10 min period daily once or on 5 consecutive days. Serotoninergic neurotransmission was followed using differential in vivo pulse voltammetry with carbon fibre electrodes measuring extracellular 5-hydroxyindoleacetic acid (5-HIAA) levels. Recordings were performed in brain areas involved in the control of behaviour, mood, and stress respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 42 publications
1
20
1
Order By: Relevance
“…Alternatively, voltammetric studies in other regions of the brain have measured extracellular 5-HIAA, which can potentially be used as an indicator of 5-HT's release, reuptake and then subsequent metabolism (Clement et al, 1998;Crespi et al, 1990;Houdouin et al, 1991). In the IC, however, we found that changes in the combined 5-HIAA+5-HT signal were not correlated with changes in the 5-HT signal during the recovery from anesthesia (Fig.3).…”
Section: Measuring 5-ht With Voltammetrymentioning
confidence: 75%
See 4 more Smart Citations
“…Alternatively, voltammetric studies in other regions of the brain have measured extracellular 5-HIAA, which can potentially be used as an indicator of 5-HT's release, reuptake and then subsequent metabolism (Clement et al, 1998;Crespi et al, 1990;Houdouin et al, 1991). In the IC, however, we found that changes in the combined 5-HIAA+5-HT signal were not correlated with changes in the 5-HT signal during the recovery from anesthesia (Fig.3).…”
Section: Measuring 5-ht With Voltammetrymentioning
confidence: 75%
“…The restricted movement manipulation (N10) was modeled after restraint-stress paradigms that are known to influence extracellular 5-HT in other regions of the brain (Bowers et al, 2007;Clement et al, 1998). Mice were contained within a small, circular arena (7.5cm diameter) within their home cage.…”
Section: Stimulimentioning
confidence: 99%
See 3 more Smart Citations